Prototype of an Android Based Online Attendance System at SMA Negeri 1 Sungai Raya - Nasihin, Muhamad; Nurcahyo, Ratih Widya (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
Student attendance at SMA Negeri 1 Sungai Raya has been recorded manually using attendance sheets signed at each meeting. This conventional method often causes various problems, such as the possibility of signature manipulation, attendance proxy, and the risk of data loss when documents are damaged or lost. In addition, the process of recapitulating attendance requires considerable time and effort, making it difficult for teachers and administrative staff. To address these issues, this study developed a prototype of an Android based online attendance system that utilizes QR codes as student attendance identifiers. The system is designed so that students can independently record their attendance by scanning QR codes, while teachers can monitor attendance in real time. Attendance data is stored online using the Firebase Cloud Firestore service, allowing attendance information to be accessed quickly and securely. The attendance system prototype was built using the Java programming language with an XML-based interface in Android Studio. The test results show that the system is capable of processing attendance data efficiently, reducing the potential for fraud, and speeding up recapitulation, making the attendance administration process more practical and accurate.